Modernitas dan Tantangannya terhadap Pelaksanaan Dakwah - Enung Asmaya (Komunika, 2015)
Modernity is viewed differently in western and eastern/Islamic culture. In western, it is associated more on the issue of secularism, the separation between religious affairs and the state. Another issue is the application of economic capitalistic system, which concerns with the material life and reduces the spirit of sharing. Besides, the development of technology has reduced the quality of interpersonal relationship and has caused worries and psychosomatics. Not all Muslims agree with these issues. However, modernity also gives spirit to the progress of Muslim society. It can make people use their optimal thinking to manage natural resources and their potentials so that they can live much better. For that reason, modernity can be a certain challenge to the Islamic preaching.